Biochemical analysis of phenotypic changes induced in cultured cells by 5-azacytidine treatment - Taylor, Shirley M (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Medical Biochemistry)) - University of Stellenbosch, 1977.